Resistance of Undisturbed Soil Microbiomes to Ceftriaxone Indicates Extended Spectrum β-Lactamase Activity - Gatica, Joao; Yang, Kun; Pagaling, Eulyn; Jurkevitch, Edouard; Yan, Tao; Cytryn, Eddie (Frontiers in Microbiology, 2015)
Emergence and spread of antibiotic resistance, and specifically resistance to third generation cephalosporins associated with extended spectrum β-lactamase (ESBL) activity, is one of the greatest epidemiological challenges of our time. In this study we addressed the impact of the third generation cephalosporin ceftriaxone on microbial activity and bacterial community composition of two physically and chemically distinct undisturbed soils in highly regulated microcosm experiments. Surprisingly, periodical irrigation of the soils with clinical doses of ceftriaxone did not affect their microbial activity; and only moderately impacted the microbial diversity (α and β) of the two soils. Corresponding slurry experiments demonstrated that the antibiotic capacity of ceftriaxone rapidly diminished in the presence of soil, and approximately 70% of this inactivation could be explained by biological activity. The biological nature of ceftriaxone degradation in soil was supported by microcosm experiments that amended model Escherichia coli strains to sterile and non-sterile soils in the presence and absence of ceftriaxone and by the ubiquitous presence of ESBL genes (blaTEM, blaCTX-M and blaOXA) in soil DNA extracts. Collectively, these results suggest that the resistance of soil microbiomes to ceftriaxone stems from biological activity and even more, from broad-spectrum β-lactamase activity; raising questions regarding the scope and clinical implications of ESBLs in soil microbiomes.